VIBRATION OF BONES: A CASE STUDY ON HUMAN FEMUR - ALMUDHAFFAR, MUJTABA; Nassar, Ameen A.; Kareem, Hani A. H. A . (Basrah Journal for Engineering Sciences, 2014)
The frequency analysis of bones is a new tool to assess bone quality or integrity to characterize osteoporosis. The modal analysis can also be used to determine failure characteristics of remodeled bone in the fractured model. This study describes the numerical characterization of the modal analysis of the standardized femur model. The objective of the numerical procedure is to identify the natural frequencies and mode shapes of an unconstrained femur. The vibration modes of the human femur are studied by digital modal analysis and finite element simulation using ANSYS version 10 programs, with respect to femur dimensions and mechanical properties. The changing of the values of free vibration natural frequencies and mode shapes of the femur due to changing of the femur densities are studied. The results are compared to those obtained experimentally. The comparison of the results shows a good agreement, which indicates that the used model can be utilized in vibration analysis of bones.